Pengaruh User Generated Content Dan E-Wom Terhadap Purchase Intention Dan Purchase Decision Pada Pembeli Produk Nyrtea Di Instagram - Faizatul Wafiyah; Any Urwatul Wusko (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
This study aims to determine the relationship of the User Generated Content and E-WOM variables to Purchase intention and Purchase Decision on Nyrtea's Instagram Followers. The sample of this study was 100 respondents who were Nyrtea Instagram followers, had respondents' criteria from the age of 17 and had made purchases through Instagram social media. Sampling techniques using the questionnaire distribution method through Google Forms. The analysis tool used in the form of SmartPLS 4.0. The results show that UGC has a positive and significant effect on purchase intention, E-WOM has a positive and significant effect on Purchase intention, UGC has no positive and significant effect on Purchase Decision, E-WOM has a positive and significant effect on Purchase Decision, Purchase intention is positive and has a positive effect significant to Purchase Decision.